Influence of vancomycin minimum inhibitory concentration on the outcome of methicillin-susceptible Staphylococcus aureus left-sided infective endocarditis treated with antistaphylococcal β-lactam antibiotics: a prospective cohort study by the International Collaboration on Endocarditis. (August 2017) - ; Athan, E.; Harris, O.; Korman, T.M.; Kotsanas, D.; Jones, P.; Reinbott, P.; Ryan, S.; Fortes, C.Q.; Garcia, P.; Jones, S.B.; Barsic, B.; et al.
Abstract: Objectives: Left-sided methicillin-susceptible Staphylococcus aureus (MSSA) endocarditis treated with cloxacillin has a poorer prognosis when the vancomycin minimum inhibitory concentration (MIC) is ≥1.5 mg/L. We aimed to validate this using the International Collaboration on Endocarditis cohort and to analyse whether specific genetic characteristics were associated with a high vancomycin MIC (≥1.5 mg/L) phenotype. Methods: All patients with left-sided MSSA infective endocarditis treated with antistaphylococcal β-lactam antibiotics between 2000 and 2006 with available isolates were included. Vancomycin MIC was determined by Etest as either high (≥1.5 mg/L) or low (<1.5 mg/L). Isolates underwent spa typing to infer clonal complexes and multiplex PCR for identifying virulence genes. Univariate analysis was performed to evaluate the association between in-hospital and 1-year mortality, and vancomycin MIC phenotype. Results: Sixty-two cases met the inclusion criteria. Vancomycin MIC was low in 28 cases (45%) and high in 34 cases (55%). No significant differences in patient demographic data or characteristics of infection were observed between patients with infective endocarditis due to high and low vancomycin MIC isolates. Isolates with high and low vancomycin MIC had similar distributions of virulence genes and clonal lineages. In-hospital and 1-year mortality did not differ significantly between the two groups (32% (9/28) vs. 27% (9/34), p 0.780; and 43% (12/28) vs. 29% (10/34), p 0.298, for low and high vancomycin MIC respectively). Conclusions: In this international cohort of patients with left-sided MSSA endocarditis treated with antistaphylococcal β-lactams, vancomycin MIC phenotype was not associated with patient demographics, clinical outcome or virulence gene repertoire.